Incidence and Risk Factors for Hypoxia in Deep Sedation of Propofol for Artificial Abortion Patients - Fang, Yiling; Xu, Yaru; Cao, Silu; Sun, Xiaoru; Zhang, Hui; Jing, Qi; Tian, Li; Li, Cheng (Frontiers in Medicine, 2022)
Background Respiratory depression is a life-threatening adverse effect of deep sedation. This study aimed to investigate the factors related to hypoxia caused by propofol during intravenous anesthesia. Methods Three hundred and eight patients who underwent painless artificial abortion in the outpatient department of Shanghai Tenth People’s Hospital between November 1, 2019 and June 30, 2020 were divided into two groups according to whether the patients experienced hypoxia (SpO2 < 95%). Preoperative anxiety assessments, anesthesia process, and operation-related information of the two groups were analyzed. The univariate analysis results were further incorporated into logistic regression analysis for multivariate analysis to determine the independent risk factors affecting hypoxia. Results Univariate analysis revealed that body mass index (BMI) (21.80 ± 2.94 vs. 21.01 ± 2.39; P = 0.038, 95% confidence interval (CI) = [−1.54, −0.04]), propofol dose (15.83 ± 3.21 vs. 14.39 ± 3.01; P = 0.002, CI = [−2.34, −0.53]), menopausal days (49.64 ± 6.03 vs. 52.14 ± 5.73; P = 0.004, CI = [0.79, 4.21]), State Anxiety Inventory score (51.19 ± 7.55 vs. 44.49 ± 8.96; P < 0.001, CI = [−9.26, −4.15]), and Self-rating Anxiety Scale score (45.86 ± 9.48 vs. 42.45 ± 9.88; P = 0.021, CI = [−6.30, −0.53]) were statistically significant risk factors for hypoxia during the operation. Logistic regression analysis showed that propofol dosage, menopausal days, and State Anxiety Inventory score were independent risk factors for hypoxia. Conclusion Patient anxiety affects the incidence of hypoxia when undergoing deep intravenous anesthesia with propofol. We can further speculate that alleviating patient anxiety can reduce the incidence of hypoxia. Clinical Trial Registration [http://www.chictr.org.cn], identifier [ChiCTR2000032167].